A Long‐Cycle‐Life Self‐Doped Polyaniline Cathode for Rechargeable Aqueous Zinc Batteries. (14th November 2018) - Shi, Hua‐Yu; Ye, Yin‐Jian; Liu, Kuan; Song, Yu; Sun, Xiaoqi
Abstract: Rechargeable aqueous zinc batteries are promising energy‐storage systems for grid applications. Highly conductive polyaniline (PANI) is a potential cathode, but it tends to deactivate in electrolytes with low acidity (i.e. pH >1) owing to deprotonation of the polymer. In this study, we synthesized a sulfo‐self‐doped PANI electrode by a facile electrochemical copolymerization process. The −SO3 − self‐dopant functions as an internal proton reservoir to ensure a highly acidic local environment and facilitate the redox process in the weakly acidic ZnSO4 electrolyte. In a full zinc cell, the self‐doped PANI cathode provided a high capacity of 180 mAh g −1, excellent rate performance of 70 % capacity retention with a 50‐fold current‐density increase, and a long cycle life of over 2000 cycles with coulombic efficiency close to 100 %. Our study opens a door for the use of conducting polymers as cathode materials for high‐performance rechargeable zinc batteries.